On the Impact of Demographic Change on Growth, Savings, and Poverty - Cruz, Marcio; Ahmed, S. Amer (World Bank, Washington, DC, 2016)
Changing population age structures are shaping the trajectories of development in many countries, bringing opportunities and challenges. While aging has been a matter of concern for upper-middle and high-income economies, rapid population growth is set to continue in the poorest countries over the coming decades. At the same time, these countries will see sustained increases in the working-age shares of their population, and these shifts have the potential to boost growth and reduce poverty. This paper describes the main mechanisms through which demographic change may affect economic outcomes, and estimates the association between changes in the share of working-age population with per capita growth, savings, and poverty rate. An increase of one percentage point in the working-age population share is found to be associated with an increase in gross domestic product per capita growth by more than one percentage point, with similarly positive effects on savings and poverty reduction.